Blast resistance of concrete slab reinforced with high performance fibre material. Issue 2 (2nd April 2016) - Li, Jun; Wu, Chengqing; Hao, Hong; Su, Yu; Liu, Zhongxian
Abstract: Concrete is now the most abundantly used material in construction. Despite good compressive strength, concrete is marked with brittleness and low tensile strength. A widely adopted method to enhance the concrete material performance especially the tensile strength and ductility is fibrous material addition. In the present study, concrete mix designs with different fibre additions have been developed, and high-performance polyethylene fibre and micro steel fibre are considered with varying volume fractions in the concrete matrix. Material static properties are obtained from laboratory tests, and further study on the dynamic performance of theses fibre reinforced concrete materials is investigated through field blast tests. Concrete slabs with high-performance polyethylene fibre reinforcement and hybrid steel and polyethylene reinforcement are casted and tested under close-in blast scenarios. Discussion on the structural damage and material performance is briefed based on the test results.